Pengaruh Motivasi Belajar dan Kecerdasan Emosional terhadap Perilaku Belajar Mahasiswa: Indonesia - Nelly Budiyarti; Henni Rahayu Handayani; Fitriyah Fitriyah (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
Learning motivation and emotional intelligence are indicators that can determine changes and improvements in student learning behavior. This study aims to analyze the influence of learning motivation and emotional intelligence partially and simultaneously on student learning behavior. This study used primary data through the distribution of questionnaires to 100 students. The data in this study were analyzed using Multiple Linear Regression. The results of the study indicate that learning motivation partially has a positive effect on learning behavior, emotional intelligence partially has a positive effect on learning behavior, and learning motivation and emotional intelligence simultaneously have a positive effect on learning behavior. The results of this study are expected to broaden students' thinking horizons and instill awareness that increasing learning motivation and emotional intelligence can improve learning behavior, which implicitly has an impact on improving student learning outcomes.